Wearable inertial sensor assessment of kinematic characteristics during unilateral jump landings in elite volleyball players with patellar tendinopathy: a cross-sectional study - Benjamin Ben Zaki; Gauthier Desmyttere; Stéphane Perrey; Marc Julia; Gilles Dusfour (BMC Sports Science, Medicine and Rehabilitation, 2026)
Abstract Background Patellar tendinopathy (PT) is a prevalent overuse injury in jumping athletes such as volleyball players, with a prevalence reaching up to 45%. It is thought to result, at least in part, from repetitive landing impacts that overload the tendon due to altered neuromuscular control and inadequate force absorption by the muscle-tendon unit. Wearable inertial sensor assessment offers an objective and field-deployable approach to characterize landing kinematics in this population. This study aimed to identify kinematic characteristics and explore kinetic variables distinguishing symptomatic from asymptomatic players with patellar tendinopathy during unilateral vertical jumps. Methods This cross-sectional study included thirty elite male volleyball players who performed single-leg countermovement jumps and single-leg drop jumps. Ten players met predefined clinical criteria for symptomatic patellar tendinopathy, including a Victorian Institute of Sport Assessment–Patellar (VISA-P) score ≤ 80, pain during single-leg decline squatting, and pain localized to the patellar tendon using pain mapping. Kinematic data were collected using 8 wearable inertial measurement units (IMUs, 100 Hz), and kinetic data using force platforms (1000 Hz). Results The PT group showed reduced knee flexion angles at initial contact, at peak, and at peak estimated vertical ground reaction force (eVGRF), predominantly during the drop jump (Benjamini-Hochberg adjusted p < 0.05; Hedges’ g = 0.82–1.60). At the ankle, dorsiflexion angle at peak eVGRF, range of motion, and peak angular acceleration were reduced, predominantly during the countermovement jump (adjusted p ≤ 0.04; Hedges’ g = 0.84–1.35). At the hip, only a smaller peak deceleration was observed during the drop jump (adjusted p = 0.04; g = -1.07). No kinetic variables or limb symmetry index differed significantly between groups. Within the PT group, greater symptom severity (lower VISA-P score) was associated with reduced flexion for knee angle at peak eVGRF during both drop-jump contacts, ankle maximum angle, and angle at peak eVGRF during the countermovement jump (ρ = 0.66–0.83, p ≤ 0.04). Conclusion These findings suggest that wearable inertial sensor-based unilateral jump-landing assessments can identify between-group kinematic differences associated with PT. Given the cross-sectional design, findings should be interpreted as descriptive rather than diagnostic, requiring confirmation in prospective studies.